2016
DOI: 10.1080/14739879.2016.1208542
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of teaching and training General Practices in England

Abstract: (max 250 words)Background: There is no national picture of teaching and training practices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Previous studies have reported higher QOF performance in GP training practices (1). QOF performance was previously reported as higher in both clinical and managerial domains (1) although we did not analyse different domains because QOF targets have evolved with much less recent focus on managerial targets.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported higher QOF performance in GP training practices (1). QOF performance was previously reported as higher in both clinical and managerial domains (1) although we did not analyse different domains because QOF targets have evolved with much less recent focus on managerial targets.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…These educational responsibilities are known to play a role in shaping the provision of care by training practices. For instance, a focus on consultation skills in workplace-based training is associated with higher reported patient satisfaction with the GP and higher overall patient experience ratings (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the inverse care law, there is an 'inverse training law', whereby there are more GP training practices in more affluent areas compared to more deprived areas [18,19]. This is partly a consequence of the increased pressures and lack of time associated with the inverse care law, and partly explained by the higher proportion of smaller, often single-handed, practices in deprived areas, which makes it more difficult to accommodate training requirements [20].…”
Section: Inverse Training Lawmentioning
confidence: 99%
“…In the UK, GPST usually involves a 3-year training programme with 18 months of this programme spent in an approved GPST practice supervised by a named GP educational supervisor. In Scotland, there are significantly more GPST training practices in affluent areas than deprived; 1,2 in England, training practices are under-represented in ethnically diverse inner-city areas; 3,4 and in France, training practices have fewer low-income patients than the national average. Size is a significant predictor of training status: 1 in Scotland, practices in deprived areas tend to be smaller.…”
Section: Introductionmentioning
confidence: 99%